Study on Virtualized Residential Gateway Tecbnology - Ming Jiang; Haolin Li; Chengbin Shen; Min Cao (Dianxin kexue)
Since the powerful function of residential gateway increased equipment costs and maintenance complexity, virtualized residential gateway technology emerged. The principle of virtualized residential gateway technology was investigated. Then two implementations of network deployment and the technical feasibility are analyzed. The CAPEX and OPEX of virtualized residential gateway were discussed compared with the existing residential gateway. Finally, with consideration of standardization and industry development, NERGˊs development trend and deployment strategy were proposed.